The association between body roundness index and new-onset hyperuricemia in Chinese population: the Kailuan cohort study - Xi Cai; Naihui Zhao; Xuemei Yang; Jiajia Ma; Yajing Liang; Yicheng Liao; Ruiyue Liu; Xinran Wen; Shuohua Chen; Guodong Wang; Na Li; Shouling Wu; et al. (BMC Public Health)
Abstract Background This study aimed to investigate the potential relationship between the newly defined adiposity metric, the Body Roundness Index (BRI), which assesses central obesity, and the development of new-onset hyperuricemia. Methods In the Kailuan cohort study from 2006 to 2019, 91,804 eligible participants were included. A multivariate Cox regression model was used to test the correlation between BRI and hyperuricemia. At the same time, the restricted cubic spline was applied to solve the dose-response relationship between BRI and the risk of hyperuricemia.Then, stratified analysis was carried out using multivariate Cox regression according to age, sex, hs-CRP level, TG level, education level, smoking status and hypertension status. Results The results showed that the risk of new-onset hyperuricemia was significantly increased in the highest quartile compared with the lowest quartile. After adjusting for confounders, compared with Q1, the HR (95% CI) for new-onset hyperuricemia was 1.24 (1.18–1.30), 1.32 (1.25–1.40), and 1.40 (1.29–1.52) for Q2, Q3, and Q4, respectively. Restricted cubic spline analysis showed a J-curve relationship between baseline BRI levels and new-onset hyperuricaemia. Age, sex, hs-CRP level, TG level, income level, education level, smoking, and hypertension each had a multiplicative interaction with BRI at baseline. Conclusion We found that elevated BRI increased the risk of developing new-onset hyperuricaemia. In addition, the association between elevated BRI and the risk of new-onset hyperuricemia showed dependency on age, sex, hs-CRP level, TG level, education level, smoking status and hypertension status.